Diversity of pollen sources used by managed honey bees in variegated landscapes. Issue 5 (19th October 2020) - Melin, Annalie; Colville, Jonathan F; Duckworth, Gregory D; Altwegg, Res; Slabbert, Ruhan; Midgley, Jeremy J; Rouget, Mathieu; S Donaldson, John
Abstract : Honey bees are the most economically important crop pollinator worldwide. They depend on a diversity of pollen for reproduction and colony growth. However, the influence of landscape composition on diversity and quantity of pollen collection by honey bees remains largely unexplored, particularly in variegated landscapes. Pollen on honey bees was trapped from 41 hives across ten sites in the Western Cape, South Africa during summer. Sampled hives were near eucalyptus trees surrounded by a high percentage of natural vegetation. Hives could therefore potentially be presented with a diverse range of flowers. To obtain a measure of relative abundance and representation of plant taxa pollen samples were collected at hives, sorted by color, weighed and DNA barcoded. Landscape analysis was performed to estimate the relative availability of the main floral resource-types and how this influenced the composition of pollen collected. Overall, eucalyptus made up the largest portion (∼49%) of pollen loads, the remainder was composed of 31 other taxa (12% native and 39% alien plants). An increase in the area of eucalyptus resulted in an increased as well as the relative amount of eucalyptus and natural pollen collected. Conversely, an increase in the area of eucalyptus resulted in a decrease in alien plant pollen and vice versa. Our results provide important quantitative evidence that shows the amount and diversity of pollen used by honey bees in summer appears to be disproportionately met by human-modified landscapes; whereas, natural vegetation, despite its large extent and diversity, performs a lower-level role during this season.